2015
DOI: 10.1007/s40830-015-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxide Layer Composition and Radial Compression on Nickel Release in Nitinol Stents

Abstract: There is a public health need to understand the effects of surface layer thickness and composition on corrosion in nickel-containing medical devices. To address this knowledge gap, five groups of Nitinol stents were manufactured by various processing methods that altered the titanium oxide layer. The following surfaces were created: [3500 nm thick mixed thermal oxide (OT), *420 nm thick mixed thermal oxide (SP), *130 nm thick mixed thermal oxide (AF), *4 nm thick native oxide (MP), and an *4 nm thick passivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 23 publications
4
52
0
Order By: Relevance
“…Since corrosion damage was not observed in NaClO-soaked EP nitinol, it was expected that no differences in nickel ion release would be observed over the two-week test. Regardless of the NaClO soak, we found that BO nitinol released more nickel than EP nitinol which agrees with previous work on laser-cut nitinol stents (Ref 5). Because nitinol performance is dependent on processing, it is difficult to speculate how a chemically etched surface or a different electropolish would respond to an NaClO soak in terms of nickel release.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Since corrosion damage was not observed in NaClO-soaked EP nitinol, it was expected that no differences in nickel ion release would be observed over the two-week test. Regardless of the NaClO soak, we found that BO nitinol released more nickel than EP nitinol which agrees with previous work on laser-cut nitinol stents (Ref 5). Because nitinol performance is dependent on processing, it is difficult to speculate how a chemically etched surface or a different electropolish would respond to an NaClO soak in terms of nickel release.…”
Section: Discussionsupporting
confidence: 92%
“…For our tests, we chose the BO and EP nitinol to attempt to bookend expected performance by having drastically different oxide thicknesses (11 nm for EP nitinol and 651 nm for BO nitinol). These oxide thicknesses are within the range of other studies on nitinol wires and stents (Ref 5, 16, 20, 21). Presumably other nitinol surface finishes would have similar or at least not worse performance after an NaClO soak.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…35 However, a recent study showed that oxide layers created by some surface treatment methods might not be as stable as previously thought. 123 In particular, a strong positive correlation between oxide layer thickness (from various methods of surface treatment) and nickel ion release was found. Furthermore, it was shown that severe mechanical deformations that Nitinol devices normally experience during deployment and function can further increase the release of nickel from the Nitinol alloy as oxide layers lack the superelastic mechanical properties and develop cracks under large strains.…”
Section: Nitinol Alloysmentioning
confidence: 95%
“…This is critical for retrieval studies whose goals are to analyze corrosion or fretting of implants such as in metal‐on‐metal orthopaedic implants or cardiovascular endovascular devices . Maintaining explant integrity is particularly important for Nitinol devices whose corrosion resistance is highly dependent on the oxide layer composition and chemistry …”
Section: Introductionmentioning
confidence: 99%